PENYALAHGUNAAN WEWENANG DALAM PENGELOLAAN IZIN PERTAMBANGAN YANG BERIMPLIKASI TINDAK PIDANA KORUPSI - Eny Suastuti; Indah Cahyani; Erma Rusdiana (Refleksi Hukum: Jurnal Ilmu Hukum, 2025)
This article examines the abuse of authority by public officials or civil servants in the mining sector in accordance with Article 3 of the Corruption Eradication Law. The Corruption Eradication Law does not provide an adequate explanation, leading to various interpretations in court decisions that create ambiguity. In addition, the concept of abuse of authority is an administrative law concept, and judicial practice shows several differences in its interpretation and parameters. The article's findings highlight challenges in enforcing Article 3 of the Corruption Eradication Law, particularly the identification of overlapping regulatory ambiguities as a significant issue. The results of the study show that including abuse of authority in Article 3 of the Corruption Eradication Law as an administrative law concept will create obstacles for law enforcement. On the other hand, the Mining Law grants the government with the authority and discretion to manage finances, from the licensing stage through implementation, including the drafting of mining cooperation contracts that must adhere to the principles of good faith and transparency.